A Comprehensive Analysis of the Clinical Significance and Underlying Oncogenic Roles of Specific MMPs in Gastric Carcinoma Reveals their Potential Roles in Prognosis and Therapy - Jin, Shiyang; Wang, Jing; Wang, Kuan (Current Molecular Medicine, 2025)
BackgroundGastric cancer is a major global cause of cancer-related deaths, necessitating investigation into Matrix Metalloproteinases’ (MMPs) diagnostic and prognostic value. Our study aimed to analyze their significance in gastric cancer.MethodsWe evaluated MMP family genes' mRNA and protein expression using the University of Alabama at Birmingham (UALCAN) and Human Protein Atlas (HPA) databases. Then, we analyzed the relationship between their mRNA expression and gastric cancer staging and survival using Gene Expression Profiling Interactive Analysis (GEPIA) and Kaplan–Meier plotter. Furthermore, we assessed this family’s gene mutation rates in gastric cancer patients using Search Tool for the Retrieval of Interaction Genes/Proteins (STRING) and explored potential pathways and mechanisms via Database for Annotation, Visualization, and Integrated Discovery (DAVID), cBioPortal, and R. Finally, we established a predictive model for gastric cancer based on these analyses to understand these genes’ roles in cancer.ResultsOur findings revealed significantly upregulated mRNA expression of MMP1/2/3/7/9/10/11/12/13/14 in gastric cancer tissues (p<0.05). Higher levels of MMP2/7/10-encoded proteins (middle or high) were observed in tumor tissues, with MMP2/11/14 closely associated with different cancer stages (p<0.05). Additionally, MMP2/7/11/14/20 mRNA levels correlated with short-term overall survival (about 20 months), while MMP1/3/9/12/13 expression was associated with favorable overall survival (about 30 months). Gastric cancer patients exhibited a 21% mutation rate of MMP family genes, which correlated with favorable overall survival. Enrichment analysis and protein-protein interaction results underscored the close association of MMPs with gastric cancer development. The MMP2 model demonstrated a significant decline in survival rates for the high expression group, with a Hazard Ratio (HR) of 1.78 (95% CI 1.47-2.16) and a log-rank P value of 2.9e-09. Statistical significance was set at p < 0.05. Univariate Cox regression identified MMP2 as a risk factor for gastric cancer patients.ConclusionOur findings highlighted MMPs' essential role in gastric cancer progression, impacting patient survival. MMP2 emerged as a promising target for gastric carcinoma detection and treatment.
Keywords: predictive modeling